Combined lipid lowering therapy, including ezetimibe, in the post-infarction period - V. E. Oleynikov; L. I. Salyamova; A. A. Chernova; A. A. Tonkoglaz; O. D. Vershinina; I. A. Babkina; N. S. Plaksin (Российский кардиологический журнал)
Aim. To study the effect of 48-week therapy with atorvastatin and ezetimibe on laboratory parameters, structural and functional arterial characteristics and heart failure markers in the post-infarction period.Material and methods. A total of 87 patients with acute myocardial infarction were included. In the first 24 hours, atorvastatin 80 mg/day was prescribed. During hospitalization, after 5-6, 24, 48 weeks, clinical and paraclinical examinations were performed. In the level of low-density lipoprotein cholesterol (LDL-C) >1,4 mmol/l and the decrease <50% at one of the follow-up visits, ezetimibe 10 mg/day was additionally prescribed.Results. Eighty participants (93%) completed the study. Patients were divided into following groups: group 1 (n=32) — atorvastatin monotherapy; group 2 (n=49) — ezetimibe and atorvastatin therapy. In group 1, LDL-C decreased after 48 weeks by 53% (p<0,001), while in group 2 by 63,2% (p<0,001). According to carotid ultrasound in group 2, a decrease in the intima media thickness after 24 and 48 weeks was revealed by 9,1% (p<0,001) and 10,5% (p<0,001) compared to the baseline value, while in group 1 — by 4,5% only on the 24th week (p=0,012). When analyzing endothelial function, there was an increase in flow-dependent vasodilation only in group 2 from 9,1 (5,6; 11,8)% to 14,3±6,8% after 48 weeks (p<0,001). With the addition of ezetimibe, there was a regression of the N-terminal pro-brain natriuretic peptide after 24 weeks by 69,6% (p=0,005), after 48 weeks — by 72,4% (p=0,009). In group 2, it decreased by 75,5% by the end of follow-up (p=0,010).Conclusion. The results rationale adding ezetimibe to statins in very high-risk patients due to the most pronounced lipid lowering effect, improvement of the structural and functional properties of the common carotid arteries, endothelial function and clinical and laboratory heart failure markers.